Socioeconomic indicators and risk of lung cancer in Central and Eastern Europe - Hrubá, Frantiska; Fabiáová, Eleonóra; Bencko, Vladimír; Cassidy, Adrian; Lissowska, Jolanta; Mates, Dana; Rudnai, Péter; Zaridze, David; Foretová, Lenka; Janout, Vladimir; Szeszenia-Dabrowska, Neonilia; Brennan, Paul; et al. (Central European journal of public health, 2009)
BACKGROUND: Social inequalities have been shown to contribute to the risk of lung cancer in industrialized countries, but it is unclear whether they also play a role in former socialist countries of Europe. METHODS: A case-control study involving 3,403 cases and 3,670 controls was conducted in Central European countries (Czech Republic, Hungary, Poland, Romania, Slovakia), Russia, and in the UK. Indicators of socioeconomic status, including education and white/blue collar occupation based on lifetime occupations were analysed as indicators of risk factors for lung cancer development, after adjustment for tobacco smoking and exposure to occupational carcinogens. RESULTS: Both indicators of socioeconomic status: low education and blue collar occupations were found as significant risk factors for lung cancer in men. The odds ratio of lung cancer for blue collar occupations compared to white collar occupations was 1.37 (95% confidence interval 1.15-1.62), that for low education compared to high education (analysis restricted to Central European countries) was 1.35 (95% confidence interval 1.03-1.77). No such effects were observed in women. CONCLUSIONS: The confirmation of the significant inverse association between the indicators of socioeconomic status and lung cancer risk in men may serve as a strong incentive for adoption of occupational and public health measures in lung cancer prevention.
Keywords: Spojené království; prevalence; senioři; Aged; Lung Neoplasms; Male; lidé; lidé středního věku; Humans; Smoking; Middle Aged; United Kingdom; socioekonomické faktory; Educational Status; nádory plic; rizikové faktory; mužské pohlaví; Socioeconomic Factors; Prevalence; Case-Control Studies; ženské pohlaví; Female; studie případů a kontrol; Europe, Eastern; stupeň vzdělání; Risk Factors; kouření; východní Evropa